2021
DOI: 10.1038/s41598-021-84070-7
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of human genetic variation on Epstein–Barr virus sequence diversity

Abstract: Epstein–Barr virus (EBV) is one of the most common viruses latently infecting humans. Little is known about the impact of human genetic variation on the large inter-individual differences observed in response to EBV infection. To search for a potential imprint of host genomic variation on the EBV sequence, we jointly analyzed paired viral and human genomic data from 268 HIV-coinfected individuals with CD4 + T cell count < 200/mm3 and elevated EBV viremia. We hypothesized that the reactivated virus circulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…One of the first studies reported associations between human genetic variants and 48 HIV-1 amino acid variants in 1071 HIV-infected patients, where all associated host SNPs mapped to the HLA class I region and none of the viral amino acids mapped to known sites of major antiretroviral drug resistance mutations 25 . Similarly, a study of Epstein-Barr virus found significant associations between human and viral sequence variation, involving three polymorphic regions in the human genome, including SNPs on chromosome 7, and a variant in the BRLF1 gene of the virus 27 . Host-pathogen co-evolution has also been proposed as an interaction mechanism for TB, however, the diversity found among Mtb differs from the viral setting.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One of the first studies reported associations between human genetic variants and 48 HIV-1 amino acid variants in 1071 HIV-infected patients, where all associated host SNPs mapped to the HLA class I region and none of the viral amino acids mapped to known sites of major antiretroviral drug resistance mutations 25 . Similarly, a study of Epstein-Barr virus found significant associations between human and viral sequence variation, involving three polymorphic regions in the human genome, including SNPs on chromosome 7, and a variant in the BRLF1 gene of the virus 27 . Host-pathogen co-evolution has also been proposed as an interaction mechanism for TB, however, the diversity found among Mtb differs from the viral setting.…”
Section: Discussionmentioning
confidence: 94%
“…Host-pathogen interaction genomics, using genome-to-genome analytical approaches, has already begun to be used to identify pathogenic mechanisms associated with other diseases, including HIV 25 , hepatitis C virus infection 26 and Epstein-Barr virus 27 . However, these approaches have not been applied to TB, where genetic studies have predominantly considered human and Mtb genomes separately.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, recent genomic analyses showed that host and viral genetic variation may affect EBV lytic reactivation. A study that analyzed paired EB viral and human genomic data from 268 human immunodeficiency virus-coinfected individuals reported significant associations between 25 human single-nucleotide polymorphisms and viral variants mapping to 3 EBV regions including BALF5 , BBRF1 , and BRLF1 [ 34 ]. These genes are involved in controlling EBV reactivation from latency and regulation of viral deoxyribonucleic acid (DNA) replication.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority of studies on EBV genotyping were limited to certain regions. Moreover, it was reported that EBV sequence variation is associated with host sequence variants, hence, joint analyses of host and viral genome variation would help decipher the pathogenesis of NPC and identify novel diagnostic and therapeutic targets ( Rüeger et al, 2021 ). Studies recruiting larger samples involving individuals with different conditions from different ethnic groups and geographical regions are needed to determine the exact association of EBV strains with the geographical distribution and development of the disease.…”
Section: Ebv Subtypesmentioning
confidence: 99%